Persamaan Evolusi Proses Semi-Markov Homogen dalam Perhitungan Premi Tambahan Asuransi Kesehatan Rawat Jalan Penyakit ISPA - , Faihatuz Zuhairoh, S.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In this thesis discussed the determination of health insurances premiums rider for outpatient respiratory disease. Respiratory disease is a disease the most treated in outpatient cases. Respiratory diseases were divided into two groups, instead of pneumonia and pneumonia are in distinguishable from the complaints of patient when a visit. The model used is a multistate model with semi-Markov assumption, expressed as a probability model of transition from one state to another state. Data was collected from a clinic located in Garut, West Java. There are two covariates of age and gender. To estimate the probability of transition between the states of used the evolution equations solution. As a result, we provide rider premium table rate categorized by the covariates.